Analisis Pengaruh Volume Penjualan Terhadap Profitabilitas Pada Usaha Matahari Cell Periode 2023–2025 - Putri Amanda Said; Andi Patimbangi; Muhammad Ardi (IKRAITH-EKONOMIKA, 2026)
This study aims to determine the effect of sales volume on profitability, projected through the Net Profit Margin (NPM), at Usaha Matahari Cell during the 2023–2025 period. This research applies a quantitative approach with an associative descriptive method. Secondary data utilized in this study consists of monthly revenue and net profit records spanning over 36 months. The data analysis technique employs simple linear regression processed using SPSS software. The descriptive analysis results indicate an average monthly turnover of Rp638,690,278, with the average NPM ranging consistently between 35%–36%. The hypothesis testing reveals that sales volume does not have a statistically significant effect on the profitability level (NPM) of Matahari Cell, indicated by a relatively minor contribution value (R-Square). This suggests that profitability in the telecommunications retail business is predominantly driven by product margin stability and efficient operational cost management, rather than merely boosting sales turnover.